SIZE RELATIONSHIP OF OOCYTES THEIR NUCLEI AND NUCLEOLUS IN CIRRHINUS REBA (HAM.) - KUMAR, KULDEEPAKI; SAREEN, M.L.; ALI, DILSHAD (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
The size relationship of oocyte, nucleus and nucleolus in Cirrhinus reba resembles fish, ascidian, amphibian and also to insect oocyte. Nucleus and nucleolus play active role during previtellogenesis. The results also indicate that nucleoli are indirectly involved in yolk formation by way of nucleolar extrusions establishing interactions between nucleus and cytoplasm in the developing oocytes.